Transformation with a gene for myo-inositol O-methyltransferase enhances the cold tolerance of Arabidopsis thaliana - B. Zhu; R. -H. Peng; A. -S. Xiong; J. Xu; X. -Y. Fu; W. Zhao; X. -F. Jin; X. -R. Meng; J. -J. Gao; R. Cai; Q. -H. Yao (Biologia Plantarum, 2012)
In this study, we report a function of myo-inositol-O-methyltransferase (Imt1) in response to low temperature stress using transgenic Arabidopsis thaliana. Imt1 gene was constructed identical to the Imt1 gene from a halophyte Mesembryanthemum crystallinum. After cold stress, the Imt1 transgenic plants exhibited stronger growth than the wild type plants. The elevated cold tolerance of the Imt1 over-expressing plants was confirmed by the lower electrolyte leakage and accumulation of malondialdehyde, but higher proline and soluble sugar contents in transgenic than wild type plants.